Role of PI4K and PI3K-AKT in ERK1/2 activation by GnRH in the Pituitary Gonadotropes - Bar-Lev, Tali H. (Mol Cell Endocrinol, 2015)
The role of PI4K and PI3K-AKT in ERK1/2 activation by GnRH was examined. A relatively long preincubation (60 min) with wortmannin (10nM and 10μM), and LY294002 (10μM and 100μM) (doses known to inhibit PI3K and PI4K, respectively), were required to inhibit GnRH-and PMA-stimulated ERK1/2 activity in αT3-1 and LβT2 gonadotrope cells. A similar preincubation protocol was required to demonstrate inhibition of IGF-1-stimulated AKT activation lending support for the need of prolonged incubation (60 min) with wortmannin in contrast to other cellular systems. To rule out that the inhibitors acted upon PI(4,5)P(2) levels, we followed the [Ca(2+)](i) response to GnRH and found that wortmannin has no significant effect on GnRH-induced [Ca(2+)](i) responses. Surprisingly, GnRH and PMA reduced, while IGF-1 increased AKT phosphorylation. We suggest that PI3K inhibits GnRH-stimulated αGSU activity, has no effect upon GnRH-stimulated LHβ activity and enhanced the GnRH-stimulated FSHβ transcription. Hence, PI4K and PI3K-AKT play a role in GnRH to ERK1/2 signaling, while PI3K may regulate also GnRH-induced gonadotropin gene expression.